Investigating Cutaneous Squamous Cell Carcinoma in vitro and in vivo: Novel 3D Tools and Animal Models - Quadri, Marika; Marconi, Alessandra; Sandhu, Simran K.; Kiss, Alexi; Efimova, Tatiana; Palazzo, Elisabetta (Frontiers in Medicine, 2022)
Cutaneous Squamous Cell Carcinoma (cSCC) represents the second most common type of skin cancer, which incidence is continuously increasing worldwide. Given its high frequency, cSCC represents a major public health problem. Therefore, to provide the best patients’ care, it is necessary having a detailed understanding of the molecular processes underlying cSCC development, progression, and invasion. Extensive efforts have been made in developing new models allowing to study the molecular pathogenesis of solid tumors, including cSCC tumors. Traditionally, in vitro studies were performed with cells grown in a two-dimensional context, which, however, does not represent the complexity of tumor in vivo. In the recent years, new in vitro models have been developed aiming to mimic the three-dimensionality (3D) of the tumor, allowing the evaluation of tumor cell-cell and tumor-microenvironment interaction in an in vivo-like setting. These models include spheroids, organotypic cultures, skin reconstructs and organoids. Although 3D models demonstrate high potential to enhance the overall knowledge in cancer research, they lack systemic components which may be solved only by using animal models. Zebrafish is emerging as an alternative xenotransplant model in cancer research, offering a high-throughput approach for drug screening and real-time in vivo imaging to study cell invasion. Moreover, several categories of mouse models were developed for pre-clinical purpose, including xeno- and syngeneic transplantation models, autochthonous models of chemically or UV-induced skin squamous carcinogenesis, and genetically engineered mouse models (GEMMs) of cSCC. These models have been instrumental in examining the molecular mechanisms of cSCC and drug response in an in vivo setting. The present review proposes an overview of in vitro, particularly 3D, and in vivo models and their application in cutaneous SCC research.